Anti-corrosion ceramic material and preparation method thereof

By modifying the eutectic technology of α-Al2O3 micropowder and titanium dioxide and zirconia, the dispersion and corrosion resistance of porous alumina ceramic materials are solved, and the mechanical properties and acid- and alkali-resistant corrosion resistance of ceramics are improved, forming high Anti-corrosion ceramic material with porosity and good bending strength.

CN119143488AActive Publication Date: 2024-12-17苏州芯合半导体材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411646510.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Porous alumina ceramic materials have shortcomings in dispersion, corrosion resistance and mechanical strength, especially in terms of poor dispersion, poor corrosion resistance and poor mechanical properties.

Method used

Reaction by adding water, polyethylene glycol and α-Al2O3 micropowder to the flask, the modified α-Al2O3 micropowder was generated, and stirred with phenylatic anhydride and pyridine, and then blended with titanium dioxide and zirconia for molding and molding. , and finally sintered in a muffle furnace, using the coordination effect of polymer and the eutectic of zirconia to form a high-stability eutectic, improving the dispersion and corrosion resistance of ceramic materials.

Benefits of technology

The dispersion and mechanical properties of ceramic materials are improved, the flexural strength is improved, and the corrosion quality loss rate in acid and alkali solution is significantly reduced, and the acid and alkali corrosion resistance of ceramic materials is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, and discloses an anti-corrosion ceramic material and a preparation method thereof.The preparation method comprises the steps that modified alpha-Al2O3 micro powder, titanium dioxide micro powder and zirconium oxide are subjected to ball milling, aging, blank pressing, sintering and other processes, and the porous alumina-based anti-corrosion ceramic material is obtained. According to the aluminum oxide ceramic material, the modified alpha-Al2O3 micro powder is used as a raw material, the polyethylene glycol-based polymer coated on the surface of the modified alpha-Al2O3 micro powder is used as a pore-forming agent, the polymer is pyrolyzed when being sintered in an air atmosphere, a rich and uniform pore structure is formed in a ceramic matrix, and the obtained aluminum oxide ceramic material still has very good bending strength while keeping relatively high porosity. Titanium dioxide is used as a sintering aid, zirconium oxide is used as a corrosion-resistant modifier, and zirconium oxide and alpha-Al2O3 form a high-stability eutectic melt in the sintering process, so that the acid and alkali corrosion resistance of the ceramic material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, in particular to an anti-corrosion ceramic material and a preparation method thereof. Background Art

[0002] Porous alumina ceramic is a porous ceramic material with excellent performance, which has the advantages of high specific surface area, good heat resistance, strong shock resistance, etc. It is widely used in shock-absorbing materials, thermal insulation materials, chemical sensors, etc. Al2O3 micropowder is mixed and sintered with a dispersant, a pore-forming agent, a sintering aid, etc. to obtain a porous alumina ceramic with excellent performance. The patent with publication number CN117430442A discloses a porous ceramic for blocking ozone penetration for gas sensor packaging and its preparation method and application. The porous ceramic sheet obtained by sintering has good ozone barrier properties, hydrophobic air permeability and high temperature and humidity resistance with calcined alumina, zinc oxide, iron oxide, chromium oxide, magnesium oxide, corn starch, methyl cellulose, polyethylene glycol, glycerol, polyvinyl alcohol, etc. as raw materials. However, the porous ceramic sheet of the patent does not show good dispersibility, mechanical strength and corrosion resistance. Summary of the invention

[0003] The invention solves the problems of poor dispersibility, poor corrosion resistance and poor mechanical properties of porous alumina ceramics.

[0004] The technical solution provided by the present invention is: a method for preparing an anti-corrosion ceramic material: (1) Add water and polyethylene glycol to a flask, stir to dissolve, then add α-Al2O3 powder, pyromellitic anhydride and pyridine, stir to react, heat and dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder. The reaction formula is: .

[0005] (2) Add water, 100 parts by weight of modified α-Al2O3 powder, 1-2 parts by weight of titanium dioxide powder, and 0.5-1.2 parts by weight of zirconium oxide into a ball mill, control the ball mill speed to 200-300 r / min, and ball mill for 10-15 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 20-25°C for 12-18 hours; then heat it to 90-100°C in an oven, and heat and dry it for 2-3 hours; then place it in a mold, and use a molding machine to press it at a pressure of 20-30 MPa for 3-5 minutes to form a green body; finally, sinter it in a muffle furnace to obtain a porous alumina-based anti-corrosion ceramic material.

[0006] Preferably, in (1), the weights of polyethylene glycol, pyromellitic anhydride and pyridine are 4-10%, 0.44-1.1% and 0.014-0.035% of the mass of α-Al2O3 powder, respectively.

[0007] Preferably, in (1), the reaction temperature is 40-50°C and the reaction time is 6-10h.

[0008] Preferably, in (2), the sintering process is to first heat the temperature to 350-400°C at a heating rate of 2-3°C / min in an air atmosphere, and keep the temperature for 30-40min; then heat the temperature to 800-950°C, and keep the temperature for 1.5-2h; and finally heat the temperature to 1200-1300°C, and keep the temperature for 2-2.5h.

[0009] The technical effect produced by the present invention is as follows: the present invention uses pyridine as a catalyst, polyethylene glycol and pyromellitic anhydride undergo a polymerization reaction to generate a polymer containing a carboxyl group, and utilizes the carboxyl group to interact with the surface of α-Al2O3 micropowder such as coordination, so that an in-situ polymerization reaction occurs on the surface of the α-Al2O3 micropowder, thereby realizing the coating modification of the α-Al2O3 micropowder by the polymer. After coating, the dispersibility of the α-Al2O3 micropowder is improved, agglomeration is suppressed, and mechanical properties such as flexural strength of the ceramic are improved.

[0010] The polyethylene glycol-based polymer coated on the surface of the modified α-Al2O3 micropowder of the present invention serves as a pore-forming agent. When sintered in an air atmosphere, the polymer undergoes thermal decomposition to form a rich and uniform pore structure in the ceramic matrix. The obtained alumina ceramic material has good bending strength while maintaining a relatively high porosity.

[0011] The present invention uses titanium dioxide as a sintering aid and zirconium oxide as a corrosion-resistant modifier, and undergoes processes such as ball milling, aging, and molding. During the sintering process, zirconium oxide and α-Al2O3 form a high-stability eutectic, which is beneficial to improving the acid and alkali corrosion resistance of the ceramic material and reducing the corrosion mass loss rate of the ceramic material in acid and alkali solutions. DETAILED DESCRIPTION

[0012] The technical scheme in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. The raw materials in the embodiments and comparative examples of the present application are all commercially available unless otherwise specified.

[0013] The average particle size of the α-Al2O3 powder of the present invention is 5.6 μm, the average particle size of the titanium dioxide powder is 200 nm, and the average particle size of the zirconium oxide powder is 600 nm.

[0014] Example 1

[0015] (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 90 mg of pyromellitic anhydride, and 2.8 mg of pyridine, heat to 45 °C, stir to react for 6 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0016] (2) Add 100 mL of water, 100 g of modified α-Al2O3 powder, 1 g of titanium dioxide powder, and 0.7 g of zirconium oxide to a ball mill, control the ball mill speed to 250 r / min, and ball mill for 15 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 h; then heat it to 90°C in an oven and dry it for 3 h; then place it in a mold and use a molding machine to press it at a pressure of 25 MPa for 5 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 350°C at a heating rate of 2°C / , and keep it warm for 40 min; then heat it to 900°C and keep it warm for 1.5 h; finally, heat it to 1300°C and keep it warm for 2 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0017] Example 2

[0018] (1) Add 300 mL of water and 1.2 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 0.13 g of pyromellitic anhydride, and 4.2 mg of pyridine, heat to 50 °C, stir to react for 10 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0019] (2) Add 120 mL of water, 100 g of modified α-Al2O3 powder, 1.5 g of titanium dioxide powder, and 0.5 g of zirconium oxide to a ball mill, control the ball mill speed to 200 r / min, and ball mill for 15 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 20°C for 18 h; then heat it to 90°C in an oven and dry it for 3 h; then place it in a mold and use a molding machine to press it at a pressure of 30 MPa for 3 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 400°C at a heating rate of 2°C / , and keep it warm for 30 min; then heat it to 950°C and keep it warm for 1.5 h; finally heat it to 1200°C, keep it warm and sinter it for 2 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0020] Example 3

[0021] (1) Add 300 mL of water and 1.6 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 0.18 g of pyromellitic anhydride, and 5.7 mg of pyridine, heat to 50 °C, stir to react for 10 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0022] (2) Add 120 mL of water, 100 g of modified α-Al2O3 powder, 1.5 g of titanium dioxide powder, and 0.85 g of zirconium oxide to a ball mill, control the ball mill speed to 300 r / min, and ball mill for 10 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 h; then heat it to 100°C in an oven and dry it for 2 h; then place it in a mold and use a molding machine to press it at a pressure of 30 MPa for 3 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 400°C at a heating rate of 3°C / , and keep it warm for 30 min; then heat it to 800°C and keep it warm for 2 h; finally heat it to 1250°C, keep it warm and sinter it for 2.5 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0023] Example 4

[0024] (1) Add 400 mL of water and 2 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 0.22 g of pyromellitic anhydride, and 7 mg of pyridine, heat to 40 °C, stir to react for 10 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0025] (2) Add 100 mL of water, 100 g of modified α-Al2O3 powder, 2 g of titanium dioxide powder, and 1.2 g of zirconium oxide to a ball mill, control the ball mill speed to 300 r / min, and ball mill for 10 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 h; then heat it to 100°C in an oven and dry it for 2 h; then place it in a mold and use a molding machine to press it at a pressure of 20 MPa for 5 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 400°C at a heating rate of 2°C / , and keep it warm for 30 min; then heat it to 850°C and keep it warm for 2 h; finally heat it to 1300°C, keep it warm for 2 h, and obtain a porous alumina-based anti-corrosion ceramic material.

[0026] Example 5

[0027] (1) Add 400 mL of water and 1.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 0.2 g of pyromellitic anhydride, and 6.2 mg of pyridine, heat to 45 °C, stir to react for 8 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0028] (2) Add 100 mL of water, 100 g of modified α-Al2O3 powder, 1.8 g of titanium dioxide powder, and 1 g of zirconium oxide to a ball mill, control the ball mill speed to 300 r / min, and ball mill for 10 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 h; then heat it to 100°C in an oven and dry it for 2 h; then place it in a mold and use a molding machine to press it at a pressure of 25 MPa for 5 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 350°C at a heating rate of 2°C / , and keep it warm for 40 min; then heat it to 850°C and keep it warm for 2 h; finally heat it to 1300°C and keep it warm for 2 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0029] Comparative Example 1 (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder and 2.8 mg of pyridine, heat to 45 °C, stir for 6 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0030] (2) Add 100 mL of water, 100 g of modified α-Al2O3 powder, 1 g of titanium dioxide powder, and 0.7 g of zirconium oxide to a ball mill, control the ball mill speed to 250 r / min, and ball mill for 15 min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 h; then heat it to 90°C in an oven and dry it for 3 h; then place it in a mold and use a molding machine to press it at a pressure of 25 MPa for 5 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 350°C at a heating rate of 2°C / , and keep it warm for 40 min; then heat it to 900°C and keep it warm for 1.5 h; finally, heat it to 1300°C and keep it warm for 2 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0031] Comparative Example 2 (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, then add 20 g of α-Al2O3 powder, 90 mg of pyromellitic anhydride, and 2.8 mg of pyridine, heat to 45 °C, stir to react for 6 h, heat to dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder.

[0032] (2) Add 100 mL of water, 100 g of modified α-Al2O3 powder and 1 g of titanium dioxide powder to a ball mill, control the ball mill speed to 250 r / min, and ball mill for 15 min; pour the ball mill liquid into a sealed bag and age it in an insulated box at 25°C for 12 h; then heat it to 90°C in an oven and dry it for 3 h; then place it in a mold and use a molding machine to press it at a pressure of 25 MPa for 5 min to make a green body; finally, in a muffle furnace, in an air atmosphere, heat it to 350°C at a heating rate of 2°C / min, and keep it warm for 40 min; then heat it to 900°C and keep it warm for 1.5 h; finally heat it to 1300°C and keep it warm for 2 h to obtain a porous alumina-based anti-corrosion ceramic material.

[0033] The three-point bending method was used to test the flexural strength of alumina ceramic samples. The sample size was 40 mm × 4 mm × 3 mm and the loading rate was 0.5 mm / min.

[0034] The porosity of alumina ceramics was tested according to the method of GB / T 1966-1996.

[0035] The acid and alkali corrosion resistance of alumina ceramics was tested according to the method of GB / T 1970-1996. The medium of the acid corrosion test was a 20% mass fraction sulfuric acid solution. The medium of the alkali corrosion test was a 1% mass fraction sodium hydroxide solution. The boiling time was 1h. The mass loss method was used to calculate the percentage of mass reduction compared to the mass before corrosion, i.e. the corrosion mass loss rate.

[0036] The performance test results are shown in Table 1.

[0037] Table 1: Performance test results

[0038] As can be seen from Table 1, Examples 1-5 utilize polyethylene glycol and pyromellitic anhydride to undergo a polymerization reaction to generate a polymer containing a carboxyl group, and utilize the carboxyl group to interact with the surface of the α-Al2O3 micropowder through coordination and the like, thereby causing an in-situ polymerization reaction on the surface of the α-Al2O3 micropowder, thereby achieving the coating modification of the α-Al2O3 micropowder by the polymer. After coating, it is beneficial to improve the dispersibility of the α-Al2O3 micropowder, inhibit agglomeration, and improve the mechanical properties of the ceramic, such as the flexural strength. At the same time, the polyethylene glycol-based polymer coated on the surface of the α-Al2O3 micropowder acts as a pore-forming agent. When sintered in an air atmosphere, the polymer undergoes pyrolysis to form a rich and uniform pore structure in the ceramic matrix. The obtained alumina ceramic material has good flexural strength while maintaining a relatively high porosity. Furthermore, titanium dioxide is used as a sintering aid and zirconium oxide is used as a corrosion resistance modifier. During the sintering process, zirconium oxide and α-Al2O3 form a highly stable eutectic, which is beneficial to improving the acid and alkali corrosion resistance of the ceramic material and reducing the corrosion mass loss rate of the ceramic material in acid and alkali solutions.

[0039] Compared with Example 1, when preparing modified α-Al2O3 in Comparative Example 1, only polyethylene glycol is added, and no pyromellitic anhydride is added. Polyethylene glycol does not contain a carboxyl group, and has a low surface interaction with α-Al2O3, making it difficult to achieve coating modification of α-Al2O3, and does not improve the dispersibility of α-Al2O3 micropowder. It is difficult to effectively inhibit agglomeration, and the porosity of the sintered ceramic material is low, and the flexural strength is low, and the mechanical properties are poor.

[0040] Compared with Example 1, Comparative Example 2 does not add zirconium oxide, and the corrosion mass loss rate of the ceramic material in acid and alkali solutions after sintering is large, and the acid and alkali corrosion resistance is poor.

[0041] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A method for preparing an anti-corrosion ceramic material, characterized in that: The preparation method is: (1) Add water and polyethylene glycol to a flask, stir to dissolve, then add α-Al2O3 powder, pyromellitic anhydride and pyridine, stir to react, heat and dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder; (2) Add water, 100 parts by weight of modified α-Al2O3 powder, 1-2 parts by weight of titanium dioxide powder, and 0.5-1.2 parts by weight of zirconium oxide into a ball mill and perform ball milling. Pour the obtained ball milling liquid into a sealed bag and age it in an insulated box. Then heat and dry it in an oven. Then place it in a mold and press it into a green body through a molding machine. Finally, sinter it in a muffle furnace to obtain a porous alumina-based anti-corrosion ceramic material.

2. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (1), the weights of polyethylene glycol, pyromellitic anhydride and pyridine are 4-10%, 0.44-1.1% and 0.014-0.035% of the mass of α-Al2O3 micropowder respectively.

3. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (1), the reaction temperature is 40-50°C and the reaction time is 6-10h.

4. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the rotation speed during ball milling is 200-300 r / min, and the time is 10-15 min.

5. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the aging temperature is 20-25°C and the aging time is 12-18 hours.

6. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the drying temperature is 90-100°C and the drying time is 2-3h.

7. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the pressure when the green body is made is 20-30 MPa and the time is 3-5 min.

8. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In (2), the sintering process is to first heat the temperature to 350-400°C in an air atmosphere at a heating rate of 2-3°C / min, and keep the temperature for 30-40min; then heat the temperature to 800-950°C and keep the temperature for 1.5-2h; and finally heat the temperature to 1200-1300°C and keep the temperature for 2-2.5h.

9. An anti-corrosion ceramic material obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ozone permeation blocking porous ceramic for gas sensor packaging as well as preparation method and application thereof

    CN117430442A

  • Method for preparing porous aluminum oxide ceramic by virtue of polyurethane

    CN109942314A

  • Method for preparing phase change latent heat material by modifying polyethylene glycol compound

    CN110591655A

  • Zirconia-doped alumina ceramic and preparation method thereof

    CN112939582A

  • High-heat-dissipation material for battery module shell and preparation method of high-heat-dissipation material

    CN117004205A